Empowering product photography skills among teenagers in Gunung Village, Boyolali Regency - Arif Surya Kusuma; Umda Garit Artiar; Alya Nur Azizah (Universitas Muhammadiyah Magelang, 2024)
Smartphones are devices equipped with numerous fascinating features, leading people to become increasingly attached to and dependent on this technology. However, in Gunung Village, there are still relatively few individuals who can utilize this medium for profitable production. One example is the utilization of the smartphone camera feature for product photography. The aim of this community service is to enhance teenagers' understanding and skills in practicing the basics of product photography using a smartphone. This enhancement enables them to present their potential products more professionally. The method employed involves providing instruction on basic photography and engaging in practical product photography sessions. The focus of this service is on processed food products from the partners. The outcomes of this service were significant, as evidenced by an average increase of 34.28% in test results regarding product photography material. Additionally, participants successfully produced product photos aligned with the objectives and techniques of product photography.